Unusual morphology of foveal Müller glia in an adult human born pre-term - Kar, Deepayan; Singireddy, Ramya; Kim, Yeon Jin; Packer, Orin; Schalek, Richard; Cao, Dongfeng; Sloan, Kenneth R.; Pollreisz, Andreas; Dacey, Dennis M.; Curcio, Christine A. (Frontiers in Cellular Neuroscience, 2024)
The fovea of human retina, a specialization for acute and color vision, features a high concentration of cone photoreceptors. A pit on the inner retinal aspect is created by the centrifugal migration of post-receptoral neurons. Foveal cells are specified early in fetal life, but the fovea reaches its final configuration postnatally. Pre-term birth retards migration resulting in a small pit, a small avascular zone, and nearly continuous inner retinal layers. To explore how Müller glia participate, we used serial-section electron microscopic reconstructions to examine the morphology and neural contacts of Müller glia contacting one foveal cone in a 28-year-old male organ donor born at 28 weeks' gestation. A small non-descript foveal avascular zone contained massed glial processes that included a novel class of 'inner' Müller glia. Like classic 'outer' Müller glia that span the retina, inner cells have bodies in the inner nuclear layer (INL), are packed with intermediate filaments, and insert processes between neurons. Unlike 'outer' Müller glia, 'inner' cells do not reach the external limiting membrane but instead terminate at the outer plexiform layer. One completely reconstructed inner cell ensheathed cone pedicles and a cone-driven circuit of midget bipolar and ganglion cells. Inner Müller glia outnumber foveal cones by 1.8-fold in the outer nuclear layer (221,448 vs 123,026 cells/mm 2 ). Cell bodies of inner Müller glia outnumber those of outer Müller glia by 1.7-fold in the INL (41,872 vs 24,631 cells/ mm 2 ). Müller glia account for 95% and 80% of the volume of the foveal floor and Henle fiber layer, respectively. Determining whether inner cells are anomalies solely resulting from retarded lateral migration of inner retinal neurons in pre-term birth requires further research.